Vicious cycle of emotion regulation and ODD symptoms among Chinese school-age children with ODD: a random intercept cross-lagged panel model - Wenrui Zhang; Yanbin Li; Longfeng Li; Stephen Hinshaw; Xiuyun Lin (BMC, 2023)
Abstract A strong link between children's emotion regulation and oppositional defiant disorder (ODD) symptoms has been documented; however, the within-person mechanisms remain unclear. Based on the self-control theory and self-regulation theory, our study investigated the longitudinal, bidirectional relationship between emotion regulation and ODD symptoms in school-age children with ODD using parent- and teacher-reported data, respectively. A total of 256 Chinese elementary school students participated in a three-wave longitudinal study spanning two years. We used the random intercept cross-lagged panel model (RI-CLPM) to investigate the concurrent and longitudinal associations between emotion regulation and ODD symptoms. Results from the RI-CLPMs revealed that ODD symptoms were negatively correlated with emotion regulation and positively correlated with emotion lability/negativity at both the between-person and within-person levels across settings. Additionally, in the school setting, emotion regulation negatively predicted subsequent ODD symptoms but not vice versa, whereas emotion lability/negativity was bidirectionally associated with ODD symptoms over time. The longitudinal associations of ODD symptoms with emotion regulation and lability/negativity were not observed in the home setting. These findings suggest a circular mechanism between children's emotion regulation and ODD symptoms and support the view that emotion regulation, particularly emotion lability/negativity, plays an important role in the development of ODD symptoms.